Fiscal policy under the eyes of wary bondholders - Ruben Marek Staffa; Gregor von Schweinitz (Halle Institute for Economic Research (IWH), 2023)
This paper studies the interaction between fiscal policy and bondholders against the backdrop of high sovereign debt levels. For our analysis, we investigate the case of Italy, a country that has dealt with high public debt levels for a long time, using a Bayesian structural VAR model. We extend a canonical three variable macro mode to include a bond market, consisting of a fiscal rule and a bond demand schedule for long-term government bonds. To identify the model in the presence of political uncertainty and forward-looking investors, we derive an external instrument for bond demand shocks from a novel news ticker data set. Our main results are threefold. First, the interaction between fiscal policy and bondholders' expectations is critical for the evolution of prices. Fiscal policy reinforces contractionary monetary policy through sustained increases in primary surpluses and investors provide incentives for 'passive' fiscal policy. Second, investors' expectations matter for inflation, and we document a Fisherian response of inflation across all maturities in response to a bond demand shock. Third, domestic politics is critical in the determination of bondholders' expectations and an increase in the perceived riskiness of sovereign debt increases inflation and thus complicates the task of controlling price growth.
Keywords: C11; E31; E43; E52; E6; 330; bond markets; fiscal policy; instrument; monetary policy; structural vector autoregression